A Systematic Literature Review of ChatGPT for Vocabulary Mastery - Diantari, Ni Luh Feby; Utami, I G A Lokita Purnamika; Artini, Ni Nyoman (EDU SOCIETY: JURNAL PENDIDIKAN, ILMU SOSIAL DAN PENGABDIAN KEPADA MASYARAKAT, 2025)
Vocabulary mastery is a fundamental component in learning English as a Foreign Language (EFL) and English as a Second Language (ESL), but students often face obstacles in understanding and remembering new vocabulary. In this study, the researcher systematically examined the use of ChatGPT in vocabulary learning and explored its influence on vocabulary development. This study uses a Systematic Literature Review (SLR) design with PRISMA guidelines. Data were collected from academic journal articles published between 2018 and 2025 through the Google Scholar database, resulting in 16 relevant studies that were analyzed based on strict inclusion criteria. The analytical result indicates that teaching using ChatGPT significantly impacts students' vocabulary acquisition in the context of EFL and ESL. ChatGPT can be effective in improving vocabulary retention through interactive explanations, contextual examples, and direct feedback. In addition, the study findings highlight an increase in student engagement, motivation, and learning independence, as well as a decrease in anxiety in language use. Despite challenges related to response accuracy and digital literacy, this study concludes that ChatGPT is a potential instructional tool when integrated with appropriate pedagogical guidance.